BRAND IMAGE BUILDING IN ISLAMIC HIGHER EDUCATION - Hasanah, Siti Ma’rifatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
The brand image of the university is cumulative perceptions of how consumers see the brand of university. It is the consumer’s experience with the brand that build images. Brand image is a crucial element that contributes to the success of an university and the highest value representing the university. State Islamic Higher Education (Perguruan Tinggi keagamaan Islam Negeri) currently faces unfavorable condition and second class image in stakeholders’s mind. So, there is a need to be aware the value of brand image building. Therefore, it is very urgent to conduct this research. This is a qualitative approach and case study type. Source of the data is derived from informants and documentation, which are adjusted to the research focus. The result of this research indicates that: (1) The brand image of UIN Maulana Malik Ibrahim Malang based on stakeholder’s perspective is quite good. According to the data, UIN Maulana Malik Ibrahim Malang is considered as an Islamic University which integrates science and religion and combines the concept of ma’had and university. (2) The strategy used by UIN Maulana Malik Ibrahim Malang is starting with building many advantages, both comparative and competitive advantages. The strategies can be described in 3 steps: building strong positioning, supporting by differentiation then promoting and communicating to the stakeholders.